Linearizing an L-band power amplifier for RADAR applications - Inácio, Ana Inês Silva (2013)
This thesis attempts to improve the linearity, while keeping the efficiency, of a given power amplifier to be used in RADAR applications. The thesis is divided in three major parts: first, the theoretical analysis around the chosen linearization technique is done by mathematical deduc-tion and MATLAB simulations. In second place, ADS simulations with low-frequency dithering applied to an amplifier model, provided by the man¬ufacturer of the amplifier, are performed. The desired characteristics found during simulations will be used on the design of the prototype. Then, using the designed prototype, measurements to compare with the previous simulations, will be done. To prove the concept idea, small and large signal, for a single-tone, and two-tone measurements, with and without dithering, will be performed. The improvement of the intermodulation distortion products using a dithered amplifier will be shown demonstrating actual linearity enhancement.